Energy management of battery to DC motor - Ahmad Syahir, Zainal (2008)
An electric vehicle (EV) is vehicles that use an electric as its power source. Electricity can be generated by many ways like solar, wind and water. An EV will produce almost zero emission. An EV used a direct current (DC) motor as exchange with the internal combustion engine (ICE) in conventional vehicle and in hybrid electric vehicle (HEV). A battery electric vehicle (BEV) is just using battery as its power source which is different from HEV that are using ICE as a generator and as a secondary power source that still produce pollution in the air. The energy for BEV is generated by battery to DC motor. This part is known as energy management of battery to DC motor. There is method to estimate the state of charge (SOC) from a battery. In this project, an experiment have be done using 5 horsepower (HP) DC motor and a lead-acid battery to estimate the SOC by using an open circuit voltage (OCV) of a battery. For charging profile, a data is produced by using a 12V 20A charger that is connected to a series of battery. A simulation for determining SOC of a battery to DC motor also have be done by using a MATLAB software version 7.6.0 (R2008a). By an experiment, result of charging and discharging profile are plotted into a graph and by a simulation using MATLAB software, graph of discharging profile is plotted and by analyzed the result, prediction of journey have been made and battery lifetime also can be determined. With this both result, a comparison have been made to both result and an algorithm is been produced consisting of an energy management of a battery to DC motor. With this algorithm, an estimation of the energy left in the batteries that have been supply to different load of DC motor should be easier. The new design of a battery charger also been introduced in this thesis. By using a L200 component, the charger system should be an intelligent circuit with additional features